Perancangan Sistem Informasi Akuntansi Kredit Konsumtif Dengan Menggunakan Software Microsoft Visual Basic 6.0 dan SQL Server 2000 Berbasis Client Service - Ridwan Setiawan; Hery Dwi Yulianto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
PT BPR Metro Asia Mandiri wich is located at Jl. Raya Soekarno-Hatta Bandung, Phone.022-7537668 Fax. 022-7537670. Int the time of executing the recording and calculating the costumer loan transacton, PT BPR Metro Asia Mandiri uses Microsoft Excel.These problems will result uneffective and unoptimal.To reduce these problems, the writer takes the title â€œPerancangan Sistem Informasi Akuntansi Kredit Konsumtif dengan Menggunakan Software Microsoft Visual Basic 6.0 dan SQL Server 2000 Berbasis Client Serverâ€. As the research design the author uses research design with primary/secondary daya, the author uses qualitative data ande quantitative data, the author uses exploratory ande descriptive research as a research method, for data collection techniques the writer uses field studies consinting of interviews, obsrvation dand literature studies, the author using process, data and output oriented methodologies. The author use the waterfall model as a system design structure. Information system degin use contxt diagrams, data flow diagrams, data dictionaries, flow diagram, normalization and Entity Relationshop Diagrams.